The I files, the truth is out there: science teachers' constructs of inquiry. Issue 4 (4th March 2019) - Bevins, Stuart; Price, Gareth; Booth, Josephine
ABSTRACT: This article is concerned with the personal constructs of science teachers about inquiry in selected schools in the Yorkshire and the Humber region of England. While there is a large volume of existing literature which advocates the use of inquiry in the science classroom to enhance students' engagement with, and learning of science, relatively few of these studies represent teachers' voice. Therefore, we believe that it is important and distinctive to report teachers' constructs of inquiry and related concerns regarding its use in the science classroom. We identify the key constructs from 10 participating teachers and discuss these amongst a backdrop of policy implications for inquiry approaches in English secondary school science classrooms. Personal Construct Theory was used to underpin the study and frame data collection and analysis. Key findings show that the teachers identify an inquiry approach as being effective in stimulating students' independent learning and interest in science but issues such as time and confidence inhibit their deployment of inquiry approaches.